Stress transfer at the nanoscale on graphene ribbons of regular geometry. Issue 30 (23rd July 2019) - Manikas, A. C.; Pastore Carbone, M. G.; Woods, C. R.; Wang, Y.; Souli, I.; Anagnostopoulos, G.; Hadjinicolaou, M.; Novoselov, K. S.; Galiotis, C.
Abstract : Experimental and theoretical investigation of true axial stress transfer on regular-exfoliated-graphene micro-ribbons which are aligned to the loading direction. Abstract : The knowledge of the mechanism of stress transfer from a polymer matrix to a 2-dimensional nano-inclusion such as a graphene flake is of paramount importance for the design and the production of effective nanocomposites. For efficient reinforcement the shape of the inclusion must be accurately controlled since the axial stress transfer from matrix to the inclusion is affected by the axial-shear coupling observed upon loading of a flake of irregular geometry. Herein, we study true axial phenomena on regular- exfoliated-graphene micro-ribbons which are perfectly aligned to the loading direction. We exploit the strain sensitivity of vibrational wave numbers in order to map point-by-point the strain built up along the length of graphene. By considering the balance of shear-to-axial forces, we identify the shear stress at the interface and develop a universal inverse-length parameter that governs the stress transfer process at the nanoscale. An important parameter that has come out of this approach is the prediction and measurement of the transfer length that is required for efficient stress in these systems.